2006
DOI: 10.1631/jzus.2006.b0215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic potential of the polyvoltine silkworm (Bombyx mori L.) germplasm and identification of parents for breeding programme

Abstract: In the present study, polyvoltine germplasm stock of Andhra Pradesh State Sericulture Research and Development, Institute (APSSRDI) was evaluated for its performance based on quantitative and qualitative traits. Twenty-one oval and 10 peanut cocoon shaped lines were reared in different seasons of the year. Since the polyvoltines are non-diapausing, six generations were reared and evaluated for various economically important traits based on evaluation index and sub-ordinate function statistical methods. Ten top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 1 publication
3
16
1
Order By: Relevance
“…All of the studied strains in here are polivoltine, are generally more resistant to climatic changes and produce considerably less silk than the mono-or bivoltine strains (Rao et al 2006). However, our data indicated that the strains from the ACESP/UEM germplasm bank are also great producers with higher RSP values, which are close to the values reported for bivoltine strains (Goel et al 2007).…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…All of the studied strains in here are polivoltine, are generally more resistant to climatic changes and produce considerably less silk than the mono-or bivoltine strains (Rao et al 2006). However, our data indicated that the strains from the ACESP/UEM germplasm bank are also great producers with higher RSP values, which are close to the values reported for bivoltine strains (Goel et al 2007).…”
Section: Methodssupporting
confidence: 80%
“…However, Strains C121-A and C122-B generated lower values for SGW (Table 2), but exhibited the greatest values of RSP, indicating the silk gland development may be uneven among different strains, especially when 5 th instars were sampled earlier in their development. The CW (1.5 g), SW (0.4 g) and RSP (18.3%) mean values obtained for all 16 strains were higher than in some of the studies available in the literature (Porto & Okamoto 2003, Porto et al 2004, Rao et al 2006.…”
Section: Methodscontrasting
confidence: 60%
“…In a study performed by Rao et al (2006) using silkworm strains from a polyvoltine germplasm bank, a mean value of 461 eggs per laying was found, which is closer to the value observed in our study. Nevertheless, pupation rates of the multi-and polyvoltine strains reached a value greater than 86%, which is higher than that observed in our study (80%).…”
Section: Biological and Productivity Analysessupporting
confidence: 89%
“…However, a lower value (14.99%) than that observed in this study was reported by Kumaresan (2007). Other strains from a Pakistani germplasm bank (Hussain et al, 2010) and a polyvoltine germplasm bank (Rao et al, 2006) Table 2. Qualitative traits related to 14 Bombyx mori strains from the UEM Brazilian Germplasm Bank.…”
Section: Biological and Productivity Analysesmentioning
confidence: 99%
“…silkworm breeds play a vital role in the success of sericulture industry. Thus the breed development and improvement is a continuous process which aims at providing suitable genotypes with desired traits (Datta, 1984;Rao et al, 2006). Enrichment of silkworm breeds / hybrids have always been one of the important factors contributing to increase the productivity in sericulture sector.…”
Section: Introduction:-mentioning
confidence: 99%